PENGOLAHAN LIMBAH SABUT KELAPA MENJADI HIASAN - Muhammad - Zaim; Refnaldi - Refnaldi; Yofita - Sandra; Rifqi Aulia Zaim (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2020)
Nagari Pakandangan is located in Padang Pariaman as an area coconut crops. Most of the villagers use the coconut fruit to full fill their daily needs. Almost no wasted  from the stems, leaves, coir, water, to the branches or leaf of coconut tree. But unfortunately  only few people know the right way to make coconut become souvenir. Through training and mentoring activities in community service or Pengabdian Kepada Masyarakat (PKM), the community is given knowledge and skills to process coconut coir waste into souvenir. People enthusiasm for this training can be seen from the number of participants who joined the activity. Initially the team provided facilities for 10 participants, but later increased to 16 participants, ranges between 18 – 45 years old, representing 5 Korong in Nagari Pakandangan. As a result, the people of Nagari Pakandangan were able to create decorative products from coconut husk waste in the form of wind chimes and stickers. Good news, considering that the training provided is used by Wali Nagari Pakandangan to maintain and continue nurturing community to success Tourism Village (DESWITA). The creation produced through the training are used as souvenirs for tourists visiting Nagari Pakandangan.